2006
DOI: 10.1002/jso.20495
|View full text |Cite
|
Sign up to set email alerts
|

Extended lymph node dissection without routine spleno-pancreatectomy for treatment of gastric cancer: Low morbidity and mortality rates in a single center series of 250 patients

Abstract: These results compete favorably with those reported after standard D-1 gastrectomy in Western patients series. D-2 gastrectomy with spleen and pancreas routine preservation can be considered a safe treatment for gastric cancer in Western patients, at least in experienced centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 23 publications
3
31
0
Order By: Relevance
“…Furthermore, recent studies conducted in the West also show the importance of hospital volume and surgeon volume, indicating that both factors are directly related to the best results in the short term [16,17]. For example, it has been reported that mortality decreased signifi cantly in hospitals performing more than 63 gastrectomies per year [18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies conducted in the West also show the importance of hospital volume and surgeon volume, indicating that both factors are directly related to the best results in the short term [16,17]. For example, it has been reported that mortality decreased signifi cantly in hospitals performing more than 63 gastrectomies per year [18].…”
Section: Discussionmentioning
confidence: 99%
“…Two European randomized studies assessing the role of extended lymph node dissection (D2) failed to show any improvement in survival [11,12], but with associated higher mortality and morbidity rates in the extended lymphadenectomy group, as a result of splenic and pancreatic resection. This result has led to a shift from routine resection of the distal pancreas and spleen to a much more selective approach [13][14][15][16]. A more recent randomized study from a Western surgical center was able to demonstrate no increase in morbidity or mortality rates with D2 lymphadenectomy [17]; this has also been reported in numerous nonrandomized studies from specialized units with an interest in gastric cancer, demonstrating that a D2 lymph node dissection can be performed safely with good outcomes [10,15,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 98%
“…Two large, prospective randomized trials performed in The Netherlands and the United Kingdom found no survival benefit for D2 over D1 lymphadenectomy [6,7]. However, there were significant problems with these studies, including a high morbidity and mortality rate in the D2 group, which was associated with inadequate surgical training, and with the frequent performance of a distal pancreatectomy and splenectomy in the D2 group, which is now considered unnecessary [8,9].…”
Section: Introductionmentioning
confidence: 99%